Late-Presenting Left-Sided Morgagni Congenital Diaphragmatic Hernia in a 9-Year-Old Male. (8th August 2011) - Kim, Jennifer M.; Couluris, Marisa; Schnapf, Bruce M.
Abstract : Congenital diaphragmatic hernias are common, primarily occurring through the foramen of Bochdalek. However, in contrast, defects through the foramen of Morgagni are much more rare. When late presentations occur, patients may be asymptomatic or may be critically ill with respiratory and gastrointestinal symptoms. In this paper, we present a 9-year-old male who presented with recurrent, vague abdominal pain, and a previously normal abdominal CT scan. Initial investigation via an abdominal radiograph demonstrated an unexpected left lower lobe abnormality. Further evaluation and management revealed this abnormality to be an unusual left-sided congenital diaphragmatic hernia that appeared through the retrosternal foramen of Morgagni, a rare occurrence.